Monitoring the content of ethyl carbamate and copper in organic and conventional cachaça (Scientia Agricola, 2020)
Ethyl carbamate (EC) (NH2COOCH2CH3) is found in cachaça, and its presence in the beverage is conspicuous for its toxicity. Copper, the metal of choice used in the construction of stills, is also considered a beverage contaminant and is often related to the presence of EC in beverages. The study aimed to monitor the quality of cachaça by measuring the presence of copper and EC, and comparing the influences of sugarcane cultivation systems on the concentration of these contaminants. The varieties, RB 867515, RB 962869 and RB 85553, were cultivated under the following management systems: planting without fertilization; organic planting; and conventional planting. For cultivation, a completely randomized design in a factorial scheme of 3 varieties × 3 managements was used as experimental planning, in 4 replications. The concentrations of copper and EC in beverages were evaluated and submitted to univariate analysis of variance (p ≤ 0.05). The organic and conventional systems presented no significant variations in copper content, both of which are recommended for the planting of sugarcane as raw material for cachaça. From amongst the varieties evaluated, RB966928 presented the lowest concentrations of copper for the organic and conventional systems, and was the most recommended for the production of cachaça. To evaluate the EC concentration (μg L–1) in the cachaças produced, all beverages were considered in accordance with national legislation. Significant differences were observed between them, but the conventional and organic systems are favored for deployment in the cultivation of sugarcane as the raw material of cachaça. The same applies to the RB966928, RB867515 and RB855453 varieties.